2014
DOI: 10.11648/j.ajhr.20140204.18
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Quality of Life of Elderly Population in Bangladesh

Abstract: Bangladesh currently experiences the significant increase of aging population with poverty and breakdown of various social and traditional bonds. So, this study was undertaken to assess the background profile, pattern of morbidity and overall quality of life (QoL) of elderly population in Bangladesh. Data were collected from 250 elderly populations (male=168, female=82) aged 60 and over from three villages of Pabna district, Bangladesh through a pre-structured questionnaire. In each domain of the World Health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
37
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(50 citation statements)
references
References 8 publications
9
37
4
Order By: Relevance
“…Age was found to be a non-significant factor related to older people of sleep problems, consistent with two other studies' results [12][13][14][15], but inconsistent with another's [16]. The inconsistency could be due to differences between participants' mean ages.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Age was found to be a non-significant factor related to older people of sleep problems, consistent with two other studies' results [12][13][14][15], but inconsistent with another's [16]. The inconsistency could be due to differences between participants' mean ages.…”
Section: Discussionsupporting
confidence: 53%
“…In China, approximately 42 percent of people aged 60 or above suffered from sleep problems [13]. In Bangladesh, about 39 percent of older people reported sleep problems [14]. In the latter study, participants reported sleep problems, but it was not evaluated by measurement instruments.…”
Section: Introductionmentioning
confidence: 92%
“…As the home care issue was not included in the national survey, data were collected using a structured questionnaire interviewing the respondents aged 60 years and above living in urban and rural area of Sylhet district. Existing research is limited in the area of role and status of elderly, identify the causes and consequences of the aging [15] with their needs, their projected distribution [1], care services and existing situation [7], their needs and health condition [16], socio-economic status even quality of elderly life [17].…”
Section: Introductionmentioning
confidence: 99%
“…Inadequate sleep can lead to difficulty sustaining attention, a slowed reply time, impairments in memory and attention, and reduced performance [5]. In Bangladesh, about 39 percent of the older persons reported sleep problems [6]. Various psychiatric problems have been linked to sleep problems in older persons [7], particularly depression [8][9].…”
Section: Introductionmentioning
confidence: 99%
“…In Bangladesh, older persons (aged 60 or above) had a 2.79 times higher risk of depression compared to middle-aged persons (aged 40-59) [13]. To reiterate, studies [6,13] have indicated that older persons in Bangladesh were suffering from sleep problems and depression. However, their sleep problems were not measured using instruments.…”
Section: Introductionmentioning
confidence: 99%